2010
DOI: 10.2337/db10-0013
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Plays a Critical Role in Proliferation and Differentiation of Human Adipose Progenitors

Abstract: OBJECTIVEGrowth of white adipose tissue takes place in normal development and in obesity. A pool of adipose progenitors is responsible for the formation of new adipocytes and for the potential of this tissue to expand in response to chronic energy overload. However, factors controlling self-renewal of human adipose progenitors are largely unknown. We investigated the expression profile and the role of activin A in this process.RESEARCH DESIGN AND METHODSExpression of INHBA/activin A was investigated in three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(185 citation statements)
references
References 39 publications
(47 reference statements)
7
172
1
Order By: Relevance
“…Another study has shown that activin A has mitogenic effects on human adipose progenitors and inhibits differentiation along an adipogenic lineage. 38 Although we did not identify significant mitogenic effects of activin A on ASC (data not shown), these findings suggest that activin A plays an important role in promoting a vascular rather than adipogenic lineage fate for ASC, in the region of an endothelial niche.…”
Section: Circulation Researchmentioning
confidence: 49%
“…Another study has shown that activin A has mitogenic effects on human adipose progenitors and inhibits differentiation along an adipogenic lineage. 38 Although we did not identify significant mitogenic effects of activin A on ASC (data not shown), these findings suggest that activin A plays an important role in promoting a vascular rather than adipogenic lineage fate for ASC, in the region of an endothelial niche.…”
Section: Circulation Researchmentioning
confidence: 49%
“…Mature adipocytes are not capable of proliferation in vivo, and their regeneration depends on proliferation of adipose progenitor cells. 38,39 A few of the factors controlling the proliferation and differentiation of preadipocytes/progenitor cells are not yet known. FGF-2 has been shown to induce preadipocyte proliferation and inhibit pre-adipocyte differentiation in vitro.…”
Section: Debels Et Almentioning
confidence: 99%
“…Multiple signals can influence whether stem cells form adipocytes, including extracellular factors such as the bone morphogenetic proteins (BMPs) (Huang et al, 2009), transforming growth factor  (TGF) (Zamani and Brown, 2010), insulinlike growth factor 1 (IGF1) (Kawai and Rosen, 2010a), interleukin 17 (IL17) (Zúñiga et al, 2010), fibroblast growth factor 1 (FGF1) (Widberg et al, 2009), FGF2 (Xiao et al, 2010) and activin (Zaragosi et al, 2010).…”
Section: Signals To Differentiatementioning
confidence: 99%